PELAKSANAAN PEMBELAJARAN TEKS DRAMA BERDASARKAN KURIKULUM 2013 DI SMPN 10 PONTIANAK - Rahimah, Rahimah; Priyadi, Antonius Totok; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to obtain information about planning, implementation, learning outcomes, and barriers to learning text of class VIII drama students based on the curriculum of 2013 at SMPN 10 Pontianak. The method used in this research is descriptive method and qualitative form. Data collection techniques used are observation techniques, interviews and documentation. The tool used to collect data in the form of observation guidelines and documentation tool in the form of mobile phones. Data analysis techniques employed data analysis techniques on sites developed by Miles Huberman. The results showed that the planning made the teacher has been well designed seen from the achievement of the criteria determined. the implementation of learning is done well although there are some learning activities that have not been maximized. Teachers' learning outcomes are not in accordance with assessment criteria because teachers do not use assessment rubrics. Barriers to learning experienced by teachers such as class mastery, time allocation, cover of learning and learning media.Â Keywords: Learning Implementation, Drama Text, Curriculum 2013Â